una questione di centimetri - Fulvio Bernardini (GEOmedia, 2016)
In the summer of 2014, concurrently with the 150th anniversary celebrations of the first ascent of the Barre des Écrins, the Union Nationale des Géomètre Experts (UNGE) with his partners Geotopo and Geomesure organized an expedition to the Massif des Écrins to make precise GPS measurements of its three summits. The expedition turned out to be an adventure and provided scientists with the first ever centimeter-level measurement of the Barre.